ADOLESCENTS’ PERCEPTION OF THEIR PARENTING CULTURE - Najihah, Wardatussani Nailatun (Universitas Islam Malang, 2023)
This study investigated the adolescents’ perception towards their parenting culture. This study is aimed to find out the culture of their parenting style. The researcher conducted this study by interviewing adolescents aged 15 to 25 years both female and male in Malang as sampling. This study uses the descriptive qualitative method since the intended result is a brief description of adolescents’ preception. The interviews used to collect the data information due to answer the research question. The finding of the study showed that most of the parents who live in Malang City mostly apply the Authoritative type of parenting style then for adolescents' perception they feel happy and don't feel pressured by their parenting culture. Moreover, The cultural background of parenting mostly uses parenting according to religious teachings and has a high level of education and a good environment.